ダイ10ジ ニホン ナンキョク チイキ カンソクタイ エットウ タイイン ノ イガクテキ コウサツ 1 キョクチ ニ オケル テユビ ノ ジュンカン ジョウキョウ ニ ツイテ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 吉川, 暢一; キッカワ, マサモト; KIKKAWA, Masamoto (国立極地研究所, 1972)
P(論文) As a member of the 10th Japanese Antarctic Research Expedition, the author spent a year (1969-1970) at Syowa Station in Antarctica. Circulatory condition and function of the fingers of the wintering members were studied. (1) Twenty-nine persons were examined and the average of their ages was 30.9 years old. (2) Outdoor temperature at Syowa Station was 0°～-5℃ in summer, -23℃ in winter. (3) The average finger-tip temperature of the members was 31.3℃ in summer, 29.8℃ in winter, and 30.4℃ during the year, and it changed in parallel with the outdoor temperature. It was found that the finger-tip temperature in Antarctica was about 4℃ lower than that in Japan. (4) Plethysmograph of the finger-tips of the members shows a low monophasic wave (3.3 mm high), and a flattened wave when the finger-tip temperature was below 25℃. Generally a high dicrotic wave (12.9 mm high) was found in Japan. (5) Pinch and adduction power of the thumb were not affected by low temperature of the finger-tip. (6) It was concluded that in Antarctica circulatory condition in the finger-tip was largely affected, but function of the finger was not much affected. departmental bulletin paper